Academias de crossfit de Mossoró: um estudo sobre a utilização da ferramenta plano de negócios como estratégia mercadológica - Morais, Andreza Rafaele Freire de (Universidade Federal Rural do Semi-Árido, 2018)
In the academic field, the knowledge of the Business Plan tool and the gymnastics companies' market are still little explored. Under that perspective, this study proposed as a general objective To analyze if the Gyms of the CrossFit modality in Mossoró which use the Business Plan tool as a marketing strategy. For this purpose, the following specific objectives were proposed: Mapping the gyms of the CrossFit modality in Mossoró; check whether CrossFit gyms use the Business Plan tool; List the benefits of using the Business Plan for the strategic positioning of the company. The applied methodology was the qualitative analysis, having as an instrument of data collection a questionnaire applied with the managers of the gyms of CrossFit mapped. From the analysis of the data it was verified that there are 5 Gyms of the modality CrossFit in Mossoró, 2 of those gyms are accredited to the brand CrossFit (®) and 3 work with the modality but are not accredited the brand. Out of the 5 gyms, 3 know the Business Plan and two do not know it.However, it was verified that the business plan used in the 3 gyms was for loan purposes, not being used as a marketing strategy tool.It was listed the benefits of the business plan as strategic positioning of the company through the literature review.
Monografia
Keywords: Academias; Plano de negócios; CrossFit; GYMS; Business plan; CrossFit; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO